Amlodipine-Atenolol Overdose Management: A Physician’s Nightmare - N. Karthik Rao, B. Jayaprakash, Navin Patil, N. R. Rau, Chaitan Jaunky, Talha Ahmed (Journal of Applied Pharmaceutical Science, 2016)
The author reports a case of a 22-year-old female, daughter of a known hypertensive patient, who happened to consume her mother’s medicine. Her mother was on a fixed drug combination (FDC) of amlodipine and atenolol. The patient was brought to the emergency department with drowsiness following ingestion of 15 tablets of amlodipine-atenolol FDC (5+ 50 mg). On evaluation, she had refractory bradycardia and hypotension along with hyperkalemia. She was managed initially with gastric lavage with activated charcoal, and subsequently with supplementation of atropine, inotropes, anti-hyperkalaemic measures, pacemaker and levosimendan.
Keywords: Amlodipine, Atenolol, Refractory bradycardia, hypotension.